2003
DOI: 10.1111/j.1475-2743.2003.tb00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions after application of inorganic fertilizer and incorporation of green manure residues

Abstract: Emissions of N 2 O were measured after application of NH 4 NO 3 fertilizer and incorporation of winter wheat and rye green manures in two ®eld experiments in southeast England. Incorporation of green manure alone resulted in temporary immobilization of soil N, small N 2 O emissions and also low availability of N for the following crop. Emissions were increased after application of inorganic fertilizer, and were further increased from integrated management treatments whereby green manure residues were incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…This effect could be a result of better environmental conditions for the mineralization of crop residues from the previous year (Chen et al, 2013). In monoculture wheat, a combination of residue inputs with a high C:N ratio (mean C:N ratio of 160.3) and mineral N fertilizer, both at seeding and dressing, may have stimulated denitrification losses from mineral N added to soil (Li et al, 2016), as residues provide an energy supply for denitrifying microorganisms (Sarkodie-Addo et al, 2003;Sanz-Cobena et al, 2014). This effect was particularly noticeable after dressing fertilization in the campaign 2, increasing fluxes in the monoculture wheat-NT treatment and changing the trend observed in the first campaign and the beginning of the second (Fig.…”
Section: Effect Of Campaign Tillage and Crop Systems On N2o Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect could be a result of better environmental conditions for the mineralization of crop residues from the previous year (Chen et al, 2013). In monoculture wheat, a combination of residue inputs with a high C:N ratio (mean C:N ratio of 160.3) and mineral N fertilizer, both at seeding and dressing, may have stimulated denitrification losses from mineral N added to soil (Li et al, 2016), as residues provide an energy supply for denitrifying microorganisms (Sarkodie-Addo et al, 2003;Sanz-Cobena et al, 2014). This effect was particularly noticeable after dressing fertilization in the campaign 2, increasing fluxes in the monoculture wheat-NT treatment and changing the trend observed in the first campaign and the beginning of the second (Fig.…”
Section: Effect Of Campaign Tillage and Crop Systems On N2o Emissionsmentioning
confidence: 99%
“…Cereal residues (high C:N ratio) can promote soil N immobilization when they are applied without an additional source of mineral N, consequently leading to a temporary reduction of N2O fluxes (Huang et al, 2004). However, other authors (Sarkodie-Addo et al, 2003) have observed an enhancement of denitrification losses when a mineral source is added together with high C:N ratio residues, providing an energy supply for denitrifying microorganisms. Addition of N fertiliser may also inhibit CH4 uptake due to the interference of enzyme activity responsible for CH 4 oxidation (CH 4 monooxygenase) with NH3 monooxygenase (Dunfield and Knowles, 1995), depending on N rate (Aronson and Helliker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…N 2 O emissions from INM systems using organic amendments with C:N near 8 (composted manures and yard waste compost) were lower or equivalent to the organic amendment treatments in most cases [19,50,51]. Conversely, when the C:N of organic amendments were around 8 which included treatments of fresh cattle manure and freshly incorporated green manure, N 2 O emissions from INM increased compared to the organic amendment treatments [52,53]. These results suggest that high C substrate availability relative to the amount of added N is an important contributor to N 2 O emissions in INM systems [54].…”
Section: Potential For Minimizing N 2 O Emissions With Inmmentioning
confidence: 95%
“…Sarkodie-Addo et al [53] compared winter rye and wheat as green manures with added ammonium nitrate and measured subsequent N 2 O emissions in one growing season in the U.K. Incorporating green manure with added inorganic N fertilizer significantly increased N 2 O emissions compared to inorganic N addition and green manure alone.…”
Section: Summary Of Field Researchmentioning
confidence: 99%
See 1 more Smart Citation